(untitled) (Research, Society and Development, 2022)
The food industry is one of the sectors that generate the most waste, with the greatest losses occurring in the fruit and vegetable processing chain. On the other hand, biodegradable films offer an alternative for sustainable packaging and increased food shelf life. Therefore, fruit and vegetable residues can be used in biodegradable films as a possibility of reducing production cost and industrial impact on the environment, and adding value to food by-products. Thus, the present work aimed to provide a detailed and updated literature review on the production of biodegradable films from fruit and vegetable waste from the food industry. As a result of the research, it was observed that the edible films and coatings produced from these wastes are great alternatives for food packaging, because they present physical, mechanical and structural characteristics similar or even improved than those of conventional films, besides adding antimicrobial, antioxidant and sustainable properties to the packaged products.